Production of monosex male nile tilapia populations of the Chitralada strain - Borges, Adalmyr Morais; Moretti, Júlio Otávio Costa; McManus, Concepta; Mariante, Arthur da Silva (Pesquisa Agropecuaria Brasileira, 2005)
The effect of high temperature on sex ratio in the Chitralada strain of Nile tilapia (Oreochromis niloticus) was tested using two experiments. Primarily, the animals were exposed to a high (35ºC) or control (27ºC) water temperature for a 28-day-period, beginning ten days after hatching. A significant difference in sex ratio was found. The highest proportion of males was in the high temperature group (72.39%), compared with the control group (62.27%). No differences were found for total length or body weight between the groups. In the second experiment, the effect of exposure times (7, 14, 21 and 28 days starting ten days post hatching) at a constant temperature of 35ºC was tested. No differences were found in sex ratio between groups. A significant difference was found between treatments for body weight and total length. In both experiments, the survival rate had a direct relationship with the occurrence of cannibalism, which was significantly higher at 35ºC. The significant temperature effect on sex ratio found in the first experiment indicates the thermosensitivity of the Chitralada strain.